Effect of VRN‐1 and PPD‐D1 genes on heading time in European bread wheat cultivars. Issue 1 (14th November 2014) - Shcherban, Andrey B.; Börner, Andreas; Salina, Elena A.; Jung, C.
Abstract The variation of the vernalization (VRN‐1) and photoperiod (PPD‐1) genes offers opportunities to adjust heading time and to maximize yield in crop species. The effect of these genes on heading time was studied based on a set of 245 predominantly spring cultivars of bread wheat from the main eco‐geographical regions of Europe. The genotypes were screened using previously published diagnostic molecular markers for detecting the dominant or recessive alleles of the major VRN‐1 loci such as: VRN‐A1, VRN‐B1, VRN‐D1 as well as PPD‐D1. We found that 91% of spring wheat cultivars contain the photoperiod sensitive PPD‐D1b allele. Photoperiod insensitive PPD‐D1a allele has been found mainly in southern region of Europe. For this region the monogenic control of vernalization by VRN‐B1 or VRN‐D1 dominant alleles is common, whereas in the remaining part of Europe, the combination of photoperiod sensitive PPD‐D1b allele with dominant VRN‐A1, VRN‐B1 and recessive vrn‐D1 alleles represents the most frequent genotype. Also, we revealed a significantly later (5–8 days) heading of the monogenically dominant genotypes at VRN‐B1 as compared to the digenic VRN‐A1 VRN‐B1 genotypes.